Initial experience of use of tolvaptan in critically ill patients with fluid overload. (6th March 2015) - Ruiz‐Ramos, J.; Gordon, M.; Cortes, M. A.; Broch, M. J.; Ramirez, P.
Abstract: What is known and objective: Positive volume balance is related with high mortality in critically ill patients. We describe our experience in the use of tolvaptan in patients with fluid overload. Case summary: Six patients in the recovery phase from septic shock were included. All patients achieved an increase in diuresis after the first day, with a median fluid balance variation of −2362 (−485 to −3447) mL. At the end of treatment, median fluid balance variation was −9080 (−26 784 to −4395) mL. What is new and Conclusion: Tolvaptan could be an option in critically ill patients with fluid overload and resistant or not treatable with conventional diuretics.